2020
DOI: 10.30901/2658-3860-2019-2-35-43
|View full text |Cite
|
Sign up to set email alerts
|

Effective resistance to leaf rust in spring bread wheat accessions among recent additions to the VIR collection

Abstract: Актуальность. Одним из важнейших факторов снижения урожайности и качества зерна мягкой пшеницы Triticum aestivum L. является поражение грибными болезнями, в том числе листовой ржавчиной (возбудитель Puccinia triticina Erikss.). Вследствие микроэволюционных процессов в популяциях возбудителей болезней сорта часто теряют свою резистентность, поэтому необ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Vavilov All-Russian Institute of Plant Genetic Resources is of great interest for the search of valuable breeding material, including wheat for resistance to harmful foliar diseases. Up until now, a large number of sources for resistance have been identified in the bread wheat collection of the VIR [34,36,[59][60][61][62][63][64][65][66][67][68][69][70][71]. However, our earlier studies have shown that many VIR bread wheat samples previously identified in scientific literature as highly resistant are susceptible to Pt, SNB, and HLB [14][15][16]72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Vavilov All-Russian Institute of Plant Genetic Resources is of great interest for the search of valuable breeding material, including wheat for resistance to harmful foliar diseases. Up until now, a large number of sources for resistance have been identified in the bread wheat collection of the VIR [34,36,[59][60][61][62][63][64][65][66][67][68][69][70][71]. However, our earlier studies have shown that many VIR bread wheat samples previously identified in scientific literature as highly resistant are susceptible to Pt, SNB, and HLB [14][15][16]72,73].…”
Section: Discussionmentioning
confidence: 99%
“…So far, 77 genes for wheat leaf resistance [18,19] have been found, but most of them are ineffective in populations of P. triticina from Russia [20,21]. At the juvenile stage, only genes Lr9, 19, 24, 41, and 47 were highly effective against the pathogen population from the Northwest Region of the Russian Federation [22], but the first three of them have already lost their effectiveness in some regions of the country [23][24][25]. In the past, a large quantity of wheat samples resistant to leaf rust at the adult stage were identified in the world [26][27][28][29][30][31][32][33][34][35][36], but evidently, they cannot be a priori regarded as valuable for breeding in the Russian Federation due to both resistance dependence on the pathogen population structure for virulence and specific for certain region environmental conditions.…”
Section: Discussionmentioning
confidence: 99%